Criminal Law Protection for Workers Dismissed by Companies Due to Forgery of Employment Termination Letters Under Law Number 11 of 2020 concerning Job Creation - Chairangga, Muhammad; Fikri, Rahul Ardian; Ramadani, Suci (Fakultas Hukum Dehasen, 2026)
The protection of labor rights is a state obligation; however, the practice of unilateral termination of employment (PHK) by companies often violates legal norms, including criminal law. This study aims to examine the regulations and forms of criminal legal protection for workers experiencing termination under Law No. 11 of 2020 concerning Job Creation using a normative juridical method. The results indicate that although the Job Creation Law does not explicitly detail criminal sanctions specific to termination, the criminal legal basis remains applicable by referring to Articles 153 and 185 of the Manpower Law and Article 28 of the Labor Union Law to address discriminatory terminations or violations of normative rights. Furthermore, administrative manipulation and document forgery during the termination process can be prosecuted under the Penal Code (KUHP) or other special laws. The primary obstacle to law enforcement lies in weak supervision and the prevalence of administrative settlements. The study recommends strengthening labor inspection and fostering synergy among law enforcement agencies to ensure effective and fair labor protection.